Strong Ion Regulatory Abilities Enable the Crab Xenograpsus testudinatus to Inhabit Highly Acidified Marine Vent Systems - Hu, Marian Y.; Guh, Ying-Jey; Shao, Yi-Ta; Kuan, Pou-Long; Chen, Guan-Lin; Lee, Jay-Ron; Jeng, Ming-Shiou; Tseng, Yung-Che (Frontiers in Physiology, 2016)
Hydrothermal vent organisms have evolved physiological adaptations to cope with extreme abiotic conditions including temperature and pH. To date, acid-base regulatory abilities of vent organisms are poorly investigated, although this physiological feature is essential for survival in low pH environments. We report the acid-base regulatory mechanisms of a hydrothermal vent crab, Xenograpsus testudinatus, endemic to highly acidic shallow-water vent habitats with average environment pH values ranging between 5.4 and 6.6. Within a few hours, X. testudinatus restores extracellular pH (pHe) in response to environmental acidification of pH 6.5 (1.78 kPa pCO2) accompanied by an increase in blood HCO3- levels from 8.8 ± 0.3 mM to 31 ± 6 mM. Branchial Na+/K+-ATPase (NKA) and V-type H+-ATPase (VHA), the major ion pumps involved in branchial acid-base regulation, showed dynamic increases in response to acidified conditions on the mRNA, protein and activity level. Immunohistochemical analyses demonstrate the presence of NKA in basolateral membranes, whereas the VHA is predominantly localized in cytoplasmic vesicles of branchial epithelial- and pillar- cells. X. testudinatus is closely related to other strong osmo-regulating brachyurans, which is also reflected in the phylogeny of the NKA. Accordingly, our results suggest that the evolution of strong ion regulatory abilities in brachyuran crabs that allowed the occupation of ecological niches in euryhaline, freshwater and terrestrial habitats are probably also linked to substantial acid-base regulatory abilities. This physiological trait allowed X. testudinatus to successfully inhabit one of the world´s most acidic marine environments.